Shaping global health policy global social policy actors and ideas about health care systems - Kaasch, Alexandra 1977- (Palgrave Macmillan, 2015)
"This book investigates global social policy in the field of health. While legal or regulatory obligations to run health systems have primarily remained at the level of national governments, the ideational and discursive exchanges about suitable models, appropriate reforms, and socially protective arrangements extends to various transnational forums across multiple scales. Using an approach that combines transnational and comparative social policy analysis with international relations, Shaping Global Health Policy assesses various global social policy actors and compares their ideas and prescriptions about national health care systems. These comprise governmental and non-governmental organisations, including the World Health Organisation, World Bank, International Labour Organisation, Organisation for Economic Cooperation and Development, World Trade Organisation, the Global Fund to Fight Aids, Tuberculosis and Malaria, G8, G20, BRICS, and CSOs ('Global Health Watch'). The book particularly focuses upon the ensemble of health provision, financing and regulation to a comprehensive system of health and social protection. How global social policy actors guide specific national health policies is illustrated with the case of Polish health care reform in transition. Crucially, the book highlights the multiplicity of actors and the importance of considering health policies across multiple scales"..
Keywords: POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations); SOCIAL SCIENCE / Disease & Health Issues; Globalisierung; Medical policy; Globalization -- Health aspects; Globale Gesundheit; Internationale Organisation; Gesundheitspolitik